A Phase II Study of Gemcitabine, Vincristine, and Cisplatin (Gvp) As Second-Line Treatment for Patients with Advanced Soft Tissue Sarcoma. Issue 43 (October 2015) - Luo, Zhiguo; Zhang, Xiaowei; Peng, Wei; Wu, Xianghua; Wang, Huijie; Yu, Hui; Wang, Jialei; Chang, Jianhua; Hong, Xiaonan
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Patients with advanced soft tissue sarcoma (aSTS) typically have a poor prognosis. Patients progressing to doxorubicin-based regimen have limited therapeutic options. Monotherapy with cytotoxic drugs appears to have only modest activity in the second-line setting. The purpose of this phase II study was to prospectively evaluate the safety and efficacy of combination regimen with gemcitabine, vincristine, and cisplatin (GVP) as a salvage treatment for patients with aSTS. Eligible patients were female with 18∼75 years old, and had aSTS that had progressed after 1 prior anthracyclines-based chemotherapy regimen. Patients were treated with 1, 000 mg/m 2 gemcitabine intravenously (IV) on days 1 and 8, 1.4 mg/m 2 (max 2 mg) vincristine IV on day 1 and 25 mg/m 2 cisplatin IV on days 1 through 3 every 21 days until disease progression, unacceptable toxicity or up to 6 cycles. The primary endpoint was progression-free survival (PFS). Secondary endpoints included overall survival (OS), over response rate (ORR) and safety. This trial was registered with www.clinicaltrials.gov (no. NCT01192633). A total of 26 patients with a median age 47 years (21–72) were recruited. ORR was 23.1% [1 complete response and 5 partial responses]. The median PFS and OS were 4.8 (95% CI, 0.1–9.5) months and 15.0 (95% CI, 6.1–23.9) months, respectively. Grade 3/4 hematologic toxicities included neutropenia (34.6%), leukopenia (23.1%), thrombocytopenia (11.5%) and anemia (3.8%). No febrile neutropenia and grade 3/4 non-hematologic toxicities occurred. The most frequent non-hematologic toxicities were nausea/vomiting (50.0%), fatigue (30.8%), and fever (11.5%). We conclude that GVP regimen is effective with a favorable safety profile as the second-line chemotherapy in aSTS patients, which warrants further investigation in a phase III study.